NATUREZA E SOCIEDADE EM HOBBES E ROUSSEAU - Amorim Becker, Michele (Prometheus - Journal of Philosophy., 2020)
In this article, we will analyze the concepts of nature and society based on the thoughts of two modern philosophers, a time when so-called contractual thinkers seek to justify the foundations of human sociability. To this end, we will discuss the concept of “state of nature” in Thomas Hobbes, for whom the fear of violent death is seen as a determining factor for the exit from a wild condition and the foundation of societies. We will also examine the concept of "state of nature" in the work of Jean-Jacques Rousseau, who already in the 18th century warned of the process of "denaturation of man" and protested against the abuses produced by him in relation to nature.